Sesame Extract Promotes Chemopreventive Effect of Hesperidin on Early Phase of Diethylnitrosamine-Initiated Hepatocarcinogenesis in Rats - Napaporn Khuanphram; Sirinya Taya; Prachya Kongtawelert; Rawiwan Wongpoomchai (MDPI AG, 2021)
The combination of natural products is an alternative approach to achieving chemopreventive potential. Accordingly, citrus hesperidin exhibits numerous biological activities, including anticarcinogenic activities, while the sesamin in sesame exhibits potent anticancer activities and lipid-lowering effects. We investigated the cancer chemopreventive effects of mixed sesame and orange seed extract (MSO) containing hesperidin and sesamin in diethylnitrosamine (DEN)-induced hepatocarcinogenesis. Rats were injected with DEN once a week for 3 weeks to induce hepatocarcinogenesis. Rats were fed with MSO and various compositions that included sesame extract (SE) and hesperidin. The 10-week administration of MSO more effectively inhibited the number and size of hepatic GST-P-positive foci than hesperidin in DEN-initiated rats. MSO and hesperidin decreased the number of PCNA-positive hepatocytes but increased the apoptotic cells in DEN-induced rats. Furthermore, MSO and its constituents suppressed hepatic triglyceride content concurrently along with the expression of fatty acid synthase. Although the 5-week administration of MSO or hesperidin did not alter hepatic, preneoplastic lesion formation in DEN-initiated rats, it alleviated DEN-induced hepatotoxicity. MSO and its applied compositions did not impact upon the cytochrome P450 system. In conclusion, sesame extract promoted the chemopreventive effect of hesperidin on DEN-induced early stage of hepatocarcinogenesis in rats. The inhibitory mechanisms are likely involved with the induction of cell apoptosis, suppression of cell proliferation and modulation of hepatic lipogenesis. This study may provide revelations in the development of alternative treatments against hepatocellular carcinoma.